Migraine prevalence: findings from the Americas’ Migraine Observatory Study (AMIGOS) - Lisicki, Marco; Munoz-Cerón, Joe; Sarmento, Elder Machado; Oliveira , Arao; Valença, Marcelo Moraes; Andrade , Juliana Ramos de; Vélez-Jiménez, Karina; Rodriguez-Leyva, Ildefonso; Giacomozzi, Alex Rodrigo Espinoza; Bancalari, Ernesto; Schubaroff, Pablo; Peres, Mario (Headache Medicine, 2024)
Introduction Ascertaining the prevalence of headache disorders is fundamental for designing effective public health strategies. Epidemiologic studies conducted in individual countries often lack consistent methodologies, limiting broader interpretation. The Americas’ Migraine Observatory Study (AMIGOS) is a Pan-American epidemiological study designed to evaluate the burden and access to treatment of migraine and other headache disorders across the Americas. Here, we present preliminary data on migraine prevalence. Objectives To describe the prevalence of migraine in the Americas using a unified sampling methodology at a specific time point. Materials and Methods Data were collected online from a sample representative of the demographic and social characteristics of each country, with a confidence level of 98% and a margin of error of 5%. We conducted both qualitative and quantitative research on key aspects of headaches among 17,037 individuals in 20 countries from Canada to Chile. Migraine diagnosis was made based on the ICHD-3 criteria. Results The overall prevalence of migraine was 9.74% (12.6% among females, 6.8% among males). The highest prevalence was observed in Brazil (14.1%), Canada (13.3%), and the United States (13.1%), while the lowest prevalence was found in Bolivia (5.6%), Paraguay (6.7%), and Guatemala (7.5%). On average, migraine sufferers reported experiencing headaches 6.5 days per month, with 14% experiencing headaches on fifteen or more days per month. Conclusion This is the first comprehensive Pan-American migraine epidemiological study. Results indicate that migraine is highly prevalent in the Americas, with significant variations among different countries. Genetic and environmental factors may explain these observed differences.